1994
DOI: 10.1017/s0022029900028375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milking interval on secretion rate and composition of camel milk in late lactation

Abstract: SummaryThe effect of milking interval on secretion rates of milk and milk constituents was studied in four milking camels during late lactation. An interval of 4 h produced the highest milk secretion rate compared with 8, 12 and 16 h intervals, and rates tended to decline with increasing milking intervals. Secretion rates of organic (lactose, SNF, fat and protein) and inorganic milk constituents (sodium, potassium, calcium and magnesium) generally followed similar patterns of decreasing secretion with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
16
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
8
16
2
Order By: Relevance
“…In spite of these variations, all farms exhibited similar response in increased milking frequency. The outline of variations in milk yield with increasing milking frequency observed in this study is steady with similar previous assessments [17] in conventional systems. The present study clearly showed the milk yield promoting effect of milking frequency in Korean Holstein dairy cows.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of these variations, all farms exhibited similar response in increased milking frequency. The outline of variations in milk yield with increasing milking frequency observed in this study is steady with similar previous assessments [17] in conventional systems. The present study clearly showed the milk yield promoting effect of milking frequency in Korean Holstein dairy cows.…”
Section: Discussionsupporting
confidence: 91%
“…ML content varied from 3.28 to 4.43% (mean, 3.86%). The current results are consistent with previous reports (Alshaikh and Salah, 1994;Gaili et al, 2000;Zeleke, 2007;Aljumaah et al, 2012).…”
Section: Factors Affecting Milk Yield and Its Compositionsupporting
confidence: 94%
“…This fact was shown in a study that total solids, fat content, and milk pH decreased by increasing milking interval, showing the greatest value at 8-hr intervals and the lowest at 24-hr intervals [32]. Similar results were obtained by Alshaikh and Salah [33] that the organic component of camel milk such as Fat, Protein, Solids-not-fat (SNF) and Lactose decreased with increasing milking intervals and concurrently the secretion rates of milk was decreased. Moreover, the results indicated that the fat content in the milk increased continuously with advanced stage of lactation.…”
Section: Camel Milk Parameters 321 Fat Contentsupporting
confidence: 71%